The Effectiveness of Red Ginger (Zingiber officinale var. rubrum) Extract Administration on Weight Reduction in Obese Mice (Mus musculus) - Muhammad Erlangga Dewantara djoharam; Andi Alamanda Irwan; Asrini Safitri; Sigit Dwi Pramono; Irna Diyana Kartika Kamaluddin (Jurnal FARMASIMED (JFM), 2026)
Background: Obesity is a complex condition influenced by various factors, including an imbalance between caloric intake and energy expenditure. Red ginger contains bioactive compounds such as gingerol, flavonoids, and essential oils that have the potential to reduce body weight through mechanisms related to fat metabolism regulation and anti-inflammatory activity. However, studies on the effectiveness of red ginger in reducing body weight in obese mice (Mus musculus) are still limited, thus further research is needed to confirm its benefits. Objective: To evaluate the effectiveness of red ginger extract in reducing body weight in obese mice (Mus musculus). Methods: This study employed a true experimental research design with full control over research variables, allowing direct observation of cause-and-effect relationships. The treatment was administered to obese mice to determine the impact of red ginger extract on body weight reduction. Results: The results showed that red ginger extract was effective in reducing the body weight of obese mice. The bioactive compounds in red ginger act through anti-obesity mechanisms, particularly by regulating fat metabolism, indicating its potential use as a phytotherapeutic agent in managing obesity. Conclusion: Administration of red ginger extract (Zingiber officinale var. rubrum) proved effective in reducing the body weight of obese mice, evidenced by a significant difference between body weight before and after treatment, with greater weight reduction observed in the treatment groups compared to the control group.